Fairness in Markets and Market Experiments - Dirk Engelmann; Jana Friedrichsen; Dorothea Kübler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Whether pro-social preferences identified in economic laboratories survive in natural market contexts is an important and contested issue. We investigate how fairness in a laboratory experiment framed explicitly as a market exchange relates to preferences for fair trade products before and after the market experiment. We find that the willingness to buy at a higher price when higher wages are paid to the worker correlates both with the choice for a fair trade product before the laboratory experiment and with whether the participants are willing to pay a positive fair trade premium, elicited at the end of the experiment. These results support the notion that fairness preferences as assessed in laboratory experiments capture preferences for fair behavior in comparable situations outside the laboratory.
Keywords: C91; D01; D91; 330; fairness; market experiments; external validity; fair trade